Предмет: Алгебра,
автор: NY1998
Решить уравнение
(х^2-5х)(х^2-5х+10)+24=0
Ответы
Автор ответа:
0
(x^2-5x)(x^2-5x+10)+24=0
Пусть x^2-5x=t, получаем исходное уравнение
t(t+10)+24=0
t^2+10t+24=0
По т. Виета подберем корни
t1+t2=-10
t1*t2=24
t1=-6
t2=-4
Возвращаемся к замене
x^2-5x=-6
x^2-5x+6=0
x1+x2=5
x1*x2=6
x1=2
x2=3
x^2-5x=-4
x^2-5x+4=0
x3+x4=5
x3*x4=4
x3=1
x4=4
Ответ: 1;4;2;3
Пусть x^2-5x=t, получаем исходное уравнение
t(t+10)+24=0
t^2+10t+24=0
По т. Виета подберем корни
t1+t2=-10
t1*t2=24
t1=-6
t2=-4
Возвращаемся к замене
x^2-5x=-6
x^2-5x+6=0
x1+x2=5
x1*x2=6
x1=2
x2=3
x^2-5x=-4
x^2-5x+4=0
x3+x4=5
x3*x4=4
x3=1
x4=4
Ответ: 1;4;2;3
Похожие вопросы